2015
DOI: 10.1021/acsnano.5b01594
|View full text |Cite
|
Sign up to set email alerts
|

Gated Luminescence Imaging of Silicon Nanoparticles

Abstract: The luminescence lifetime of nanocrystalline silicon is typically on the order of microseconds, significantly longer than the nanosecond lifetimes exhibited by fluorescent molecules naturally present in cells and tissues. Time-gated imaging, where the image is acquired at a time after termination of an excitation pulse, allows discrimination of a silicon nanoparticle probe from these endogenous signals. Because of the microsecond time scale for silicon emission, time-gated imaging is relatively simple to imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 67 publications
3
100
0
Order By: Relevance
“…Time-gated luminescence imaging of the long-lived photoluminescence signal from the pSiNPs 23 (Fig. 5e and f) showed that intravenously injected CARG-conjugated pSiNPs (CARG-pSiNPs) accumulated in infected lungs at markedly higher levels than control-pSiNPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-gated luminescence imaging of the long-lived photoluminescence signal from the pSiNPs 23 (Fig. 5e and f) showed that intravenously injected CARG-conjugated pSiNPs (CARG-pSiNPs) accumulated in infected lungs at markedly higher levels than control-pSiNPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The time-gated method images the intrinsic, long-lived photoluminescence from the pSiNP carrier and eliminates tissue autofluorescence, 23 and allows the payload to be reliably quantified in intact organs. The quantitation of %ID/g of elemental silicon in different organs measured by ICP-OES showed a significantly higher accumulation of CARG-pSiNPs in the infected lungs than of control pSiNPs (> 4-fold).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grafting of the PEG linkers and targeting peptides slightly increased the mean hydrodynamic diameter of the nanocarriers to ~190 nm (measured by DLS, polydispersity index < 0.2). 53 When incubated with Neuro-2a cells, confocal microscopy indicated significant uptake of the RVG peptide-conjugated pSiNPs (Fig. 3a).…”
mentioning
confidence: 93%
“…Nanoparticles can be fab-ricated from a wide variety of materials, including polymers, liposomes, inorganics, and metals [Gurny, 1981;Park et al, 2009;Papastefanaki et al, 2015;Saxena et al, 2015]. Due to the vast differences among these materials, there is a broad range of functions and applications for nanoparticles; they are utilized for imaging, cell identification, cell targeting, and drug delivery [Sun et al, 2008;Ruoslahti et al, 2010;Chan et al, 2013;Joo et al, 2015;Accomasso et al, 2016]. Advances in chemistry, biology, engineering, materials science, pharmaceutics, and physics have allowed for the development of innovative nanoparticles with different shapes, sizes, surface chemistries, and cargoes.…”
Section: Introductionmentioning
confidence: 99%